Communication rules for nursing staff using messengers - I. V. Ostrovskaya; Yu. S. Korzhavina (Здоровье мегаполиса, 2023)
The relevance of the study is related to the fact that people use the same manner of communicating online outside of work and at work. However, it is necessary to develop and implement rules of communication in team chats, so that they assist nurses in work and do not lead to information overload. To identify the rules of online communication in nursing teams, authors conducted a questionnaire survey of 393 nurses from Moscow medical organizations. Survey data were processed with descriptive statistics methods and statistical inference methods (Student's t-test, Pearson's correlation coefficient). According to the respondents, the WhatsApp messenger is the most convenient tool for work communication. It was revealed that the heads of nursing teams are in dire need of establishing rules for online communication. Their need to establish rules is significantly higher than the need of employees (t-observed = 2.8 > t-critical = 1.96 at p-value ≤ 0.05). Respondents stated that the most relevant rules of communication in chats today are to write personal questions in a private message and not to a group chat; to observe the rules of grammar and spelling of the Russian language; to mark relevant messages when replying; to write about the need for feedback in the message. The rules should ensure that online information is simple, clear, trustworthy, relevant, and also has a neutral tone and takes into account the characteristics of other chat members.